Utilizing a Post-discharge Telephone Call in Outpatient Parenteral Antimicrobial Therapy (OPAT): Findings from a Quality Improvement Project. (4th October 2017) - Felder, Kimberly; Vaz, Louise; Barnes, Penelope; Varley, Cara
Abstract: Background: Transitions of care from hospitals to outpatient settings, especially for patients requiring outpatient parenteral antimicrobial therapy (OPAT) are complex. OPAT complications, such as adverse antimicrobial reactions, vascular access problems, and hospital readmissions are common. Data from transitions of care literature suggest that post-discharge telephone calls (TCs) may significantly decrease re-hospitalization but no studies have assessed the utility of post-discharge TCs as an OPAT program quality improvement process. Methods: Adult OPAT patients discharged from our hospital between April 1, 2015 and May 31, 2016 were queried for post-discharge concerns. TCs to patients or their caregivers were administered by trained medical assistants within the Department of Infectious Diseases using a standardized script and documented in the electronic medical record (EMR). Feasibility was assessed using call completion rate. The type and frequency of reported issues were analyzed by retrospective chart review. Results: 636 of 689 eligible adult OPAT patients or their caregivers received a TC with responses to scripted questions documented in the EMR (92% completion rate). 302 patients (47%) reported 319 issues, including 293 (92%) relevant to OPAT. Antimicrobial issues included diarrhea/stool changes (58; 9%); nausea/vomiting (27; 4%); and missed antimicrobial doses (22; 3%). Vascular access issues included line patency concerns (21; 3%); vascular access dressing problems (17; 2.6%) and arm pain/swelling (6; 1%). OPAT vendor issues included delays in lab or line care services (23; 4%) and OPAT orders reported as lost/not received (21; 3%). Other ID-related issues included fevers/chills/sweats (27; 4%), wound concerns (16; 2.5%), and pain (15; 2.5%). Conclusion: Adding a post-discharge TC to an OPAT program was feasible and resulted in frequent and early identification of significant OPAT patient and caregiver concerns. Findings suggest potential high-yield topics for process improvement, as well as anticipatory guidance and patient education in OPAT. Further evaluation and analysis of optimal hospital discharge processes and care coordination in OPAT, as well as their impact on post-discharge adverse events, is needed. Disclosures: All authors: No reported disclosures.